Mathematical Model for Thermal Processes of Single-Core Power Cable - D. I. Zalizny; S. N. Prohorenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes a mathematical model for thermal processes that permits to calculate non-stationary thermal processes of core insulation and surface of a single-core power cable in real-time mode. The model presents the cable as four thermal homogeneous bodies: core, basic insulation, protective sheath and internal environment. Thermal processes between homogeneous bodies are described by a system of four differential equations. The paper contains a proposal to solve this system of equations with the help of a thermal equivalent circuit and the Laplace transform. All design ratios for thermal parameters and algorithm for calculating temperature of core insulation and temperature of power cable surface. These algorithms can be added in the software of microprocessor devices. The paper contains results of experimental investigations and reveals that an absolute error of the mathematical model does not exceed 3ºС.